LEGAL NATURE OF GROUP LAWSUIT IN THE ECONOMIC RULE-MAKING - Білько, Олександр Павлович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2018)
Purpose: in the article the theoretical and legal questions of group lawsuit are examined in the economic rule-making on the basis of analysis of norms of current legislation and scientific looks of home scientists. Methods: multiplicity and judicial participation are analysed in economic спорах. Led decisions of group lawsuit, types of participation. Results: the ways of perfection of господарсько-процесуального legislation are offered. Discussion: problems of economic legislation and requirement in his perfection.